Comparing outcomes of children and youth with fetal alcohol spectrum disorder (FASD) in the child welfare system to those in other living situations in Canada: Results from the Canadian National FASD Database. (26th October 2020) - Burns, Jessica; Badry, Dorothy E.; Harding, Kelly D.; Roberts, Nicole; Unsworth, Kathy; Cook, Jocelynn L.
Abstract: Aims: The current study aimed to explore differences in adverse outcomes between youth and adolescents with fetal alcohol spectrum disorder (FASD) living in child welfare care (i.e., foster care or group home) with those living with their biological parent(s) or with adoptive or other family member(s) in Canada. Methods: Data gathered from the Canadian National FASD Database were used for analysis. A total of 665 youth and adolescents with a clinical diagnosis of FASD under the age of 18 living in child welfare care, with biological, adoptive or other family members, were included in the sample. Key areas examined included living situation, legal problems, experience of sexual or physical abuse, mental health (anxiety, conduct disorder, mood disorder and post‐traumatic stress disorder) and suicidal ideation. Descriptive statistics and chi‐square comparisons were utilized to explore these differences. Results: Results revealed a significantly higher rate of reported sexual and physical abuse among individuals in child welfare care compared with those living with biological parents or with adoptive or other family member(s). Rates of difficulty with the law were also higher among those in child welfare care compared with adoptive/other family members. Conversely, the rate of mood disorders was significantly higher among those living with adoptive/other family members compared with child welfare care. Results highlight similar rates of reported suicidal ideation/attempts across all living situations, as well as mental health concerns. Conclusions: Results offer rare insight into the lives of youth and adolescents under age 18 with diagnosed FASD who reside in child welfare care in contrast to those living with biological parent(s) or with adoptive or other family members. These findings increase our awareness of the complexity of mental health concerns and suicide risk across all living environments. Results have further implications for policy, practice and clinical intervention.